Percepção sobre hipertensão arterial e seus fatores de risco em comunidades ribeirinhas da Região Amazônica - SANTOS, Nathalia Kely Teixeira Vieira Menezes dos (2019)
Hypertension is a chronic disease that affects the silent majority of the population, in addition, hypertension is a major risk factor for development of cardiovascular, cerebrovascular and renal diseases which are with high incidence of deaths. This is a descriptive study with a qualitative approach, performed in coastal communities through Travel Program "Light in the Amazon" in order to describe the perception that hypertensive bordering this region have about HA. The research was conducted in two stages the first with a socioeconomic questionnaire and the second stage with subjective questionnaires applied only to riparian hypertensive. Responses developed through the analysis of the results left three units, namely: "Knowledge of Hypertension; Experience of hypertensive factors causing pressure elevation and the look of the riverside on the importance of prevention and treatment of disease." Know about the knowledge of riparian hypertensive, their ideas and their questions are needed to provide individualized care and propose a health intervention, taking into account the needs and peculiarities of this specific population. Through the responses of riparian hypertensive find that they have acquired knowledge with their experiences with hypertension on symptoms, however distorted thinking about hypertension and can not distinguish symptoms of the risk factors of the disease. Thus to have excellent health of the local population, the nursing professional as well as a good multidisciplinary health team is essential. Because through them can be made intervention strategies, encouraging people to associate their actions with the ways of seeing, feeling and answer their own life situations, so as to reflect on your health and lead to seeking alternative paths to transformation situations that will lead a better quality of life. In this respect, the role of nurses is essential, because care is considered a guiding principle of profession.